Audit of caesarian deliveries in a tertiary care center, in rural Bangalore, India - Saxena, Rajiv K.; Balan, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The Robson’s Ten-Group Classification System allows critical analysis of caesarean deliveries according to characteristics of pregnancy. The objective was to analyze caesarean section rates in a rural tertiary care teaching hospital in Bangalore, using Robson’s ten groups classification. Methods: This study was done in MVJ Medical College and Research Hospital, a rural tertiary care teaching hospital. All patients who underwent caesarean delivery, between November 2017 and October 2018, were included in the study. Women were classified in 10 groups according to Robson’s classification. For each group, authors calculated its relative contribution to the overall caesarean rate. Results: The overall caesarean section rate was 46.7%. The main contributors to this high caesarean rate were primiparous women in spontaneous labour (group 1) and women with previous caesarean section (group 5). 52.1% of CS were conducted on women who were unbooked or booked at a peripheral health facility and referred to present institution due to complications in labor. Strategies to lower CS rates would include encouraging women with previous CS, to undergo trial of labor to reduce CS rates for group 5C. Sensitization of staff in peripheral medical facilities for early referral of high-risk pregnancies to a tertiary care center for better control of medical complications like hypertensive disorders of diabetes mellitus. Other strategies include offering external cephalic version to eligible women with breech presentation and consider offering vaginal breech delivery to suitable women in groups 6 and 7. Conclusions: The Robson’s classification is easy to use. It is time to implement obstetric audit to lower the overall CS rates.